Virtual Colonoscopy A Practical Guide - Lefere, P.; Gryspeerdt, S. (Medical Radiology, Diagnostic Imaging, 2010)
Virtual colonoscopy, or CT colonography, is a rapidly evolving technique for the detection of tumoral lesions in the colon. It is now accepted by the American Cancer Society as a valuable screening tool for both colorectal cancer and its adenomatous precursor. Virtual colonoscopy requires state-of-the-art technique with rigorous preparation, colonic distension, and optimization of scanning parameters. Dedicated reading, analysis, and reporting of the data sets are mandatory. With contributions from a number of leaders in the field, this book addresses all the important issues relating to virtual colonoscopy. There is a particular focus on practical aspects: how to start virtual colonoscopy in your department, the regular preparation, the importance of fecal tagging, how to reduce the preparation, how to obtain optimal colonic distension, and the correct scanning parameters. Imaging characteristics and pitfalls are considered in detail, with an extensive pictorial review of difficult lesions; the importance of computer-aided diagnosis is also discussed. In this second edition the text has been updated with the latest study results and developments in technology and new illustrations have been included. This book will be invaluable to every radiologist seeking information on how to perform the exciting technique of virtual colonoscopy.